Evaluation of the Implementation of the “SIMPUS” Dental Medical Record and Human Identification System in Semarang City - Sukendro, Sulur Joyo; Cahyati, Widya Hary; Rahayu, Sri Ratna; Suhito, Hanif Pandu (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
The evaluation of the